1997
DOI: 10.1093/oxfordjournals.jbchem.a021793
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Affinity for DNA between HMG Proteins 1 and 2 Determined by Surface Plasmon Resonance Measurements

Abstract: High mobility group (HMG) proteins 1 and 2 contain two similar but non-identical repeats of DNA-binding domains and an acidic C-terminal. The proposed functions of HMG proteins 1 and 2 imply a probable difference in their DNA-binding abilities. The primary studies by gel retardation assay showed that HMG2 has higher affinity than HMG1 for supercoiled and linear DNA. The DNA-binding of HMG2 appeared strong enough to allow exchange with HMG1 molecule already bound to DNA, while the DNA-binding region of HMG1 sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…The use of a biotin-SA linker for immobilization of oligonucleotides for studies of protein:DNA binding using columns and gels has been well proven in a number of experiments to allow the immobilized dsDNAs to remain active and selective in their protein binding [7,[12][13][14][15][16][17][18][19][20][21][22][23]. To our knowledge this is the first demonstration d the use of a biotin-SA linker for immobilization of oligonucleotides to study protein:DNA binding with a planar dsDNA monolayer.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a biotin-SA linker for immobilization of oligonucleotides for studies of protein:DNA binding using columns and gels has been well proven in a number of experiments to allow the immobilized dsDNAs to remain active and selective in their protein binding [7,[12][13][14][15][16][17][18][19][20][21][22][23]. To our knowledge this is the first demonstration d the use of a biotin-SA linker for immobilization of oligonucleotides to study protein:DNA binding with a planar dsDNA monolayer.…”
Section: Discussionmentioning
confidence: 99%
“…10 K2 s K1 (k off ). 72 Stopped-flow kinetic studies of the binding of the HMG-1A domain to cis-platinmodified DNA showed that the association rate is near the diffusion limit. Similarly, dissociation rates of cis-platin-modified DNA complexes are significantly faster than those of the unmodified DNA complexes.…”
Section: Sry Tail Functions As a Kinetic Clampmentioning
confidence: 99%
“…As in LEF-1, [45][46][47][48] the SRY tail augments specific DNA binding and bending, but in SRY these effects are modest: DNA binding is reduced by less than twofold and DNA bending by only 7-108. Further, binding of the tail does not damp long-range fluctuations in DNA 42 Ribbon model of protein is shown in green (HMG box) and red (tail; residues [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]. DNA is shown as gray sticks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three biotinylated oligomers, (TTAGGG) 6 , (TTAGGG) 3 , and TTAGGG, were immobilized in separate flow channels of a sensor chip (SA, AmershamPharmacia Biotech). The in vitro interaction with purified B1, B0b and single-strand binding proteins (SSBs) of E. coli (Pharmacia Biotech) were monitored and analyzed using a ver2.1 BIAevaluation software to calculate dissociation and association rate constants (17). The electrophoretic mobility shift assay was also performed to determine the dissociation constants.…”
Section: Kinetic Analysis Of Binding With Telomeric Repeatsmentioning
confidence: 99%